KARAKTERISASI TELUR IKAN TERBANG (TOBIKO) SUMBER POLYUNSATURATED FATTY ACIDS SEBAGAI PANGAN FUNGSIONAL - Yusuf, Muhammad; Attahmid, Nur Fitriani Usdyana; Saleh, Rahmawati; Pabbenteng, P (Journal Galung Tropika, 2019)
Fish protein concentrates a resulting product by removes fat and water, in high protein concentrations. Mostly this product is applied to food that gets tall carbohydrates. Making fish protein concentrate is to constitute development innovation forms easy protein to be applied to food product gets low protein. The use of by-products, for example, fish eggs as a source of protein for functional food has not been widely carried out. An understanding of the chemical characteristics of flying fish eggs is very important. Previous research on fish eggs has become the basis for researching the chemical characteristics of flying fish eggs. Information about the levels of fatty acids, amino acids, total carotenoids, and ?-tocopherols of flying fish eggs has not been done. This research was expected to help the utilization of these commodities optimally. The purpose of this study was to determine the levels of fatty acids, amino acids, total carotenoids, and ?-tocopherol eggs of flying fish. This study was divided into 2 phases. The first step was a characterization of flying fish eggs using proximate analysis, tocopherol analysis, amino acid, and fatty acid analysis. The second step was followed by making flying fish protein concentrate followed by organoleptic testing, proximate analysis and degree of white flour concentrate. The best results in the extraction solvent with isopropyl alcohol (IPA) for 3 hours and belongs to type b for concentrated protein egg fish. KPTI is generated has the ability absorption of water, oil, emulsion and capacity density of kamba is good for additional materials, substitution and binder material for application-based products for the food high-protein food. KPTI has the amino acids essential and non-essential was very beneficial to the body.